2009
DOI: 10.1111/j.1742-1241.2006.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic gastric mucosa (inlet patch): endoscopic prevalence, histopathological, demographical and clinical characteristics

Abstract: Prevalence of HGM was 3.6%. Dysphagia was found related with the size of HGM. This may be associated with larger HGMs' causing more acid secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 22 publications
(30 reference statements)
4
50
0
7
Order By: Relevance
“…The prevalence of GIP in several large series of adults has ranged from 1.7-3.6% [22][23][24] and in the sole pediatric study it was reported to be 5.9% of 407 endoscopies. 4 The prevalence of the identification of GIP seems to be linked to the degree of awareness of the endoscopist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of GIP in several large series of adults has ranged from 1.7-3.6% [22][23][24] and in the sole pediatric study it was reported to be 5.9% of 407 endoscopies. 4 The prevalence of the identification of GIP seems to be linked to the degree of awareness of the endoscopist.…”
Section: Discussionmentioning
confidence: 99%
“…25 This prompts us to be more vigilant about identifying these lesions especially during examination of the proximal esophagus. The severity of dysphagia has also been linked to the size of the GIP in adults 24 and a higher association of respiratory symptoms has been reported in children with GIP. 4 Current treatment anecdotally consists of PPI, but no intervention studies have been described for GIP in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pese a que actualmente hay pocos estudios que comparan los síntomas entre los pacientes con y sin MGHEC, algunos muestran que en quienes sí tienen la heterotopía gástrica en el esófago cervical hay un número significativamente mayor de síntomas laringofaríngeos (9,12,19,20,21), siendo los más estudiados disfagia, odinofagia, globus faríngeo, regurgitación, tos crónica, carraspera crónica y pirosis.…”
Section: Discussionunclassified
“…HGM is a benign pathology which has also been described as cervical inlet patch as it is located just distal to upper esophageal sphincter. The prevalence of HGM has been variable reported in patients presenting with upper gastrointestinal symptoms from 1.67 to 3.6 % [4,5,6]. HGM has been regarded as a congenital anomaly by many authors, while some consider it to be related to gastroesophageal reflux disease (GERD) and hence associated with Barrett's esophagus [7,8].…”
Section: Discussionmentioning
confidence: 99%